Trade Liberalization, Exports and Imports in Syria. (May 2017) - Mohsen, Adel Shakeeb; Chua, Soo Y.; Sab, Che Normee Che
This study attempts to investigate the effect of trade liberalization on exports and imports in Syria over the period 1980–2010. Trade openness is used as an indicator of trade liberalization. The cointegration test shows that trade openness has a positive effect on exports and imports. The Granger causality test indicates that there are bidirectional short-run causality relationships between trade openness and exports, and unidirectional short-run causality relationship running from trade openness to imports. In the long run, there is unidirectional long-run causality relationship running from exports to trade openness, and no long-run causality relationship between trade openness and imports. However, trade openness tends to have a greater effect on imports than exports.